Rapid Regeneration of a Neoartery with Elastic Lamellae. Issue 47 (17th October 2022) - Wang, Ziyu; Mithieux, Suzanne M.; Vindin, Howard; Wang, Yiwei; Zhang, Miao; Liu, Linyang; Zbinden, Jacob; Blum, Kevin M.; Yi, Tai; Matsuzaki, Yuichi; Oveissi, Farshad; Akdemir, Reyda; et al.
Abstract: Native arteries contain a distinctive intima‐media composed of organized elastin and an adventitia containing mature collagen fibrils. In contrast, implanted biodegradable small‐diameter vascular grafts do not present spatially regenerated, organized elastin. The elastin‐containing structures within the intima‐media region encompass the elastic lamellae (EL) and internal elastic lamina (IEL) and are crucial for normal arterial function. Here, the development of a novel electrospun small‐diameter vascular graft that facilitates de novo formation of a structurally appropriate elastin‐containing intima‐media region following implantation is described. The graft comprises a non‐porous microstructure characterized by tropoelastin fibers that are embedded in a PGS matrix. After implantation in mouse abdominal aorta, the graft develops distinct cell and extracellular matrix profiles that approximate the native adventitia and intima‐media by 8 weeks. Within the newly formed intima‐media region there are circumferentially aligned smooth muscle cell layers that alternate with multiple EL similar to that found in the arterial wall. By 8 months, the developed adventitia region contains mature collagen fibrils and the neoartery presents a distinct IEL with thickness comparable to that in mouse abdominal aorta. It is proposed that this new class of material can generate the critically required, organized elastin needed for arterial regeneration. Abstract : Neoartery regenerated from a non‐porous graft fabricated from tropoelastin and polyglycerol sebacate displays cellular and extracellular matrix structures approximating the adventitia and intima‐media in native mouse aorta. The adventitia contains mature collagen fibrils. Within the intima‐media, an internal elastic lamina is surrounded by multiple elastic lamellae sandwiched between circumferentially aligned smooth muscle cell layers.